Heroines of film and television : portrayals in popular culture - Jones, Norma, 1972-; Bajac-Carter, Maja, 1979-; Batchelor, Bob (Lanham : Rowan & Littlefield, 2014)
"Award-winning authors from a variety from a variety of disciplines examine the changing roles of heroic women across time. In this volume, editors Norma Jones, Maja Bajac-Carter, and Bob Batchelor have assembled a collection of essays that broaden our understanding of how heroines are portrayed across media, offering readers new ways to understand, perceive, and think about women. Contributors bring fresh readings to popular films and television shows such as 'The Girl with the Drago Tattoo', 'Kill Bill', 'Buffy the Vampire Slayer', 'Weeds', 'Mad Men', and 'Star Trek'.
The erotic heroine and the politics of gender at work: a feminist reading of Mad Men's Joan Harris / Suzy D'Enbeau and Patrice M. Buzzanell -- Burn one down: Nancy Botwin as (post)feminist (anti)heroine / Katie Snyder -- Choosing her "fae"te: subversive sexuality and Lost Girl's Re/evolutionary female hero / Jennifer K. Stuller -- Torture, rape, action heroines, and The Girl with the Dragon Tattoo / Jeffrey A. Brown -- The maternal hero in Tarantino's Kill Bill / Maura Grady -- We've seen this deadly web before: repackaging the femme fatale and representing the superhero(ine) as neo-noir "black widow" in Sin City / Ryan Castillo and Katie Gibson -- Romance, comedy, conspiracy: the paranoid heroine in contemporary romantic comedy / Pedro Ponce -- Conflicted hybridity: negotiating the warrior princess archetype in Willow / Cassandra Bausman -- The woman who fell from the sky: Cowboys and Aliens' hybrid heroine / Cynthia J. Miller -- Her story, too: Final Fantasy X, Revolutionary Girl Utena, and the feminist hero's journey / Catherine Bailey Kyle -- Bollywood marriages: portrayals of matrimony in Hindi popular cinema / Rekha Sharma and Carol A. Savery -- The enduring woman: race, revenge, and self-determination in Chloe, Love Is Calling You / Robin R. Means Coleman -- The dark, twisted magical girls: Shojo heroines in Puella Magi Madoka Magica / Lien Fan Shen -- Women on the quarterdeck: the female captain as adventure hero, 1994-2009 / A. Bowdoin Van Riper -- The girl who lived: reading Harry Potter as a sacrificial and loving heroine / Norma Jones -- "It's about power and it's about women": gender and the political economy of superheroes in Wonder Woman and Buffy the Vampire Slayer / Carolyn Cocca.
Includes index.
Includes bibliographical references and index.
Keywords: Women in motion pictures; Women on television; Heroines in motion pictures; Heroines on television; Heroines in motion pictures; Heroines on television; Women in motion pictures; Women on television; Film; Fernsehfilm; Heldin; Frau; Geschlechterrolle; Kvinnor i Tv